Metaphysics of Ibn Sina - Rohman Amirul (IJCRE - International Journal of Culture, Religion, and Education, 2025)
This article analyzes IbnSina’s metaphysical views particularly the concepts of being and soul and their relevance to Islamic education. Using library research through classical and contemporary philosophical sources, the study examines IbnSina’s distinction between necessary and possible beings, as well as his tripartite model of the human soul supported by the active intellect. The analysis shows that these metaphysical principles provide a foundation for holistic Islamic education that integrates intellectual development with moral formation and spiritual awareness.